Optimal Portfolio Analysis Using the Markowitz Model: A Case Study in Mining Industry Companies Listed on the Indonesia Stock Exchange - Budiandriani Budiandriani; Wahyuni Tommo Sarira; Nurhasimah Nurhasimah; Sitti Zalsamala Maulina Manjas; Rafiuddin Rafiuddin (Universitas Muhammadiyah Makassar, 2025)
This study aims to test. Optimal Portfolio Using the Markowitz Model: Case Study in Mining Industry Companies Listed on the Indonesia Stock Exchange. This study uses Secondary data needed in this study is the Annual Report data of Mining Industry Companies Listed on the Indonesia Stock Exchange in 2021 - 2023 from the official website of each company. Sampling of respondents was carried out by purposive sampling. Purposive sampling is the selection of samples based on assessment. This analysis is assisted by Microsoft Excel software. The results of the study show that the portfolio with maximum profit consists of ICNO 2.93, ENRG 0.32, TINS -0.23, MEDC 0.01, PSAB -1.24, IFSH 3.01, ANTM 1.65, MBAP 0.09, and PTBA 1.40. The expected return of the portfolio is 0.66 with a risk of 0.22. This optimal portfolio is better than a portfolio filled with 10 stocks with the same weight, where the expected return increases from 0.21 to 0.66 and the standard deviation decreases from 0.29 to 0.22. This shows that allocating funds using the optimal portfolio is more effective than equalizing the weights on each stock.